KINERJA DAN PENGEMBANGAN DIRI GURU RA AL FALLAH KARANGTENGAH DEMAK - Ulya, Fitrotul; Noor, Fu’ad Arif (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
AbstractThis study aims to find a description of the performance and development of teachers of RA Al Falah Sampang Karangtengah Demak. The core of the study is focused on the factors that affect teacher performance, while the factors examined in this study are teacher performance and development. The research method used is qualitative research methods. The data collection technique used in this study was a survey data collection tool. Respondents in this study were permanent teachers at the RA Al Falah Sampang Karangtengah foundation. Data analysis techniques used simple regression. The results of this study indicate: (1) Teacher performance and development are in the quite effective category, and teacher performance is in the high enough category; (2) teacher development has a positive effect on performance. The key to the success of learning with a distance or online system is collaboration between parents and teachers. Because these two figures have the most role in learning activities. If in the past maybe the old onrang just took their children to school, then went home and came back to pick them up again. Now all matters are almost the task of parents, even teaching children to do learning tasks also requires parental assistance.